2020
DOI: 10.3389/fcimb.2019.00444
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in the Gut Microbiota Modify Brain Lipid Composition

Abstract: Understanding the molecular mechanisms underlying the changes observed during aging is a prerequisite to design strategies to prevent age-related diseases. Aging is associated with metabolic changes, including alteration in the brain lipid metabolism. These alterations may contribute to the development of pathophysiological conditions. Modifications in the gut microbiota composition are also observed during aging. As communication axes exist between the gut microbiota and the brain and knowing that microbiota … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 79 publications
2
38
0
Order By: Relevance
“…In summary, the HF/TFA-rich diets could induce obesity, adverse serum parameters, modifications of lipid profiles in the brain and plasma and gut dysbiosis. Based on the hypotheses of Mohammed et al (24) and Albouery et al (26) , we speculated that dietary TFA might lead to modifications of insulin level in the serum and lipid profiles in the brain and plasma through the gut microbiota. All of the results demonstrated links between the HF/TFA-DIO and dysfunction of the gut microbiota, including adverse blood and brain parameters, an increase in Bacteroidetes, a decrease in Muribaculaceae, etc.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In summary, the HF/TFA-rich diets could induce obesity, adverse serum parameters, modifications of lipid profiles in the brain and plasma and gut dysbiosis. Based on the hypotheses of Mohammed et al (24) and Albouery et al (26) , we speculated that dietary TFA might lead to modifications of insulin level in the serum and lipid profiles in the brain and plasma through the gut microbiota. All of the results demonstrated links between the HF/TFA-DIO and dysfunction of the gut microbiota, including adverse blood and brain parameters, an increase in Bacteroidetes, a decrease in Muribaculaceae, etc.…”
Section: Resultsmentioning
confidence: 98%
“…The results of Phivilay et al (25) support this phenomenon, indicating that most TFA are produced at the expense of decreases in linoleic acid. In addition, Albouery et al (26) pointed out that intestinal colonisation by a microbiota profoundly modified the brain lipid composition. Our study showed that TFA could lead to modifications of lipid profiles in the brain and plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies also posit that gut microbes can modulate the host’s lipidome. For instance, Albouery et al investigated how colonization of germ-free (GF) mice by the fecal microbiota of young or old donor mice impacted the lipid content of the brain and liver [ 12 ]. Mice receiving fecal bacteria from aged mice exhibited increased total monounsaturated fatty acids, and a reduction in the relative amounts of cholesterol and total polyunsaturated fatty acids in the brain cortex.…”
Section: Lipid Pool Of the Human Gutmentioning
confidence: 99%
“…The genomic DNA of gut microbiota was extracted from murine cecal contents, and 16S rRNA genes in the DNA samples were analyzed using a MiSeq sequencer (Illumina, San Diego, CA, USA) Microbiome analysis were performed by Biomnigene company (www.biomnigene.fr, Besançon, France), as previously reported [36]. Briefly, microbial genomic DNA was extracted using the E.Z.N.A Stool DNA kit (Omega Bio-tek, Norcross, GA, USA) following the manufacturer's instructions.…”
Section: Fecal Microbiota Analysis By 16s Rrna Gene Sequencingmentioning
confidence: 99%